Optimalisasi model pembelajaran direct intruction terhadap keterampilan guling depan pada siswa sekolah dasar - ekatarani, khristyana; Mochamad Ridwan; Fransisca Januarumi Marhaendra Wijaya (Physical Education Departement of University PGRI Jombang, 2025)
The learning model is a form designed to support learning in schools in this case the direct instruction learning model in other words direct learning which is a learning model that is applied procedurally and structured, the purpose of the study is to see the optimal direct instruction learning model used for front roll skills. This study uses experimental research with a quantitative research approach, the sample for this study is fourth grade students at Suko 2 State Elementary School with a total of 53 students and sampling with purposive sampling, the design uses One Group Pre-test Post-test Design data collection with front roll skills tests, data analysed descriptively and paired simple t test. The results of the study for the pre-test with a min value of 5.00, max 8.00, mean 6.5283, standard deviation 0.89020. Meanwhile, the post test data results show a min value of 5.00, max 8.00, mean 7.3774, for a standard deviation of 0.71324. As for the different test results, the sig value is 0.00 <0.05. The conclusion that it can be said that the application of the direct instruction model is optimal for the front roll skills of Suko 2 State Elementary School students